2016
DOI: 10.1111/bcp.13075
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic crash risk associated with benzodiazepine and z‐hypnotic use after implementation of a colour‐graded pictogram: a responsibility study

Abstract: AIMSTo assess potential change in medicine exposure and association with the risk of road traffic crash across a time period that started before the implementation of a grading system warning of the effect of medicine on driving performance. METHODSData from three French national databases were extracted and matched: the national health care insurance database, police reports and the national police database of injurious crashes. Drivers involved in such crashes in France, from July 2005 to December 2011 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The previous analysis of 2005–2011 data suggested an increase in exposure to benzodiazepine anxiolytics and z-hypnotics in 2010–2011 (Orriols et al, 2016). The follow-up conducted as part of this study in subsequent years showed that the use of these prescription drugs among drivers involved in a road traffic crash is stabilizing.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The previous analysis of 2005–2011 data suggested an increase in exposure to benzodiazepine anxiolytics and z-hypnotics in 2010–2011 (Orriols et al, 2016). The follow-up conducted as part of this study in subsequent years showed that the use of these prescription drugs among drivers involved in a road traffic crash is stabilizing.…”
Section: Resultsmentioning
confidence: 97%
“…Due to their high levels of consumption and association with crash risk, the two classes most represented in terms of attributable fraction were benzodiazepine anxiolytics and z-hypnotics (zolpidem and zopiclone) (Barbone et al, 1998; Chang et al, 2013; Engeland et al, 2007; Gjerde et al, 2015; Gustavsen et al, 2008; Hemmelgarn et al, 1997; Orriols et al, 2011; Ravera et al, 2011; Smink et al, 2010). A first observation of exposure trends to benzodiazepine anxiolytics and z-hypnotics among drivers involved in road traffic crashes was made, suggesting a transient downward trend in exposure following the implementation of the color-graded pictogram system (Orriols et al, 2016). Given that consumption levels of psychotropic prescription drugs are likely to change rapidly, particularly among drivers whose average age is increasing, it seems necessary to continue to monitor the level of exposure to prescription drugs and the resulting risk of road traffic crashes.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the use of various analytical methods for sensitivity analyses, studies have concerned the determination of the denominator in case-population studies 27 or the effect of exposures to different drug classes and risk of car accidents, [48][49][50][51] using links to external registries 52 and original analytical methods. 53 There are other groups working on similar ventures.…”
Section: Other (Methodological Research)mentioning
confidence: 99%
“…Hypnotics increase sleepiness. Several epidemiological studies have highlighted an association between the use of benzodiazepines or "Z-drugs" (Zopiclone and Zolpidem) and increased accidents [22][23][24][25]. A review of 27 controlled studies confirmed an increased accident risk for Zolpidem, Zopiclone, Temazepam, Diazepam, Flunitrazepam, Flurazepam, Lorazepam, and Triazolam [26] volunteers and driving simulators have confirmed this risk, which has been shown to be dependent on the dose, time between the dose and the test and the half-life of the hypnotic [27][28][29].…”
Section: Hypnotic Usementioning
confidence: 99%